Sedation of Pediatric Patients during Dermatosurgery - Arjun Prakashey; Bhushan Madke; Sandeep Kulkarni; Amar Taksande; Aishwarya Ashokbhai Ramani (Wolters Kluwer Medknow Publications, 2024)
Executing dermatosurgical procedures can be a challenging task in the pediatric population due to their hyperreactive and hypermobile behavioral responses to discomfort posed by these procedures. Thus, most of the dermatological procedures are to be performed in minimal or moderate (conscious) sedation. The objective of this review is to compare the different sedative drugs used in pediatric patients to achieve cooperation during a standard dermatological procedure. Other traditional methods of ensuring compliance by feeding and distracting the patient will be discussed briefly to help or add on to current knowledge in sedation of children during dermatosurgery. While sedatives can be effective in managing anxiety and pain in pediatric dermatosurgery, their use should be carefully considered given the potential adverse effects and risks involved in indiscriminate use and the decision to use sedatives should be individually tailored, considering factors such as the child's age, medical history, and the nature of procedure being performed.